Cellular Stress Responses and Gut Microbiota in Inflammatory Bowel Disease - Siyan “Stewart” Cao (Gastroenterology Research and Practice)
Progresses in the past two decades have greatly expanded our understanding of inflammatory bowel disease (IBD), an incurable disease with multifaceted and challenging clinical manifestations. The pathogenesis of IBD involves multiple processes on the cellular level, which include the stress response signaling such as endoplasmic reticulum (ER) stress, oxidative stress, and hypoxia. Under physiological conditions, the stress responses play key roles in cell survival, mucosal barrier integrity, and immunomodulation. However, they can also cause energy depletion, trigger cell death and tissue injury, promote inflammatory response, and drive the progression of clinical disease. In recent years, gut microflora has emerged as an essential pathogenic factor and therapeutic target for IBD. Altered compositional and metabolic profiles of gut microbiota, termed dysbiosis, are associated with IBD. Recent studies, although limited, have shed light on how ER stress, oxidative stress, and hypoxic stress interact with gut microorganisms, a potential source of stress in the microenvironment of gastrointestinal tract. Our knowledge of cellular stress responses in intestinal homeostasis as well as their cross-talks with gut microbiome will further our understanding of the pathogenesis of inflammatory bowel disease and probably open avenues for new therapies.